Living Hadith And Dialectic Of Social Texts: An Analysis of The Practice of Marriage on Eid in Javanese Culture - Alfi, Imam; Maarif Hidayat1, Imam; Solahudin, Solahudin (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study examines the concept of Living Hadith as a dynamic response to the problems of modern people, by combining the authenticity of hadith texts and the contextual needs of society. Through a qualitative approach and literature study of written sources, this study analyzes the application of Living Hadith in Javanese culture, especially in traditions such as weddings on holidays. The results of the study show that Living Hadith not only reinforces the relevance of the Sunnah of the Prophet in the contemporary era but also offers an adaptive model of hadith understanding without eroding its basic authority. These findings make a significant contribution to the development of hadith studies by mapping the dialectic between the establishment of religious texts and socio-cultural dynamics. The tradition of marriage during Eid al-Fitr/Adha in Java is an example of Living Hadith, adapting Islamic values to local culture even without a specific textual basis. This practice combines the concept of holiday blessings and Javanese togetherness, showing the flexibility of applying hadith in a social context as long as it does not contradict sharia. Living Hadith proves the dynamics of the interaction of religious texts with local traditions, maintaining the authority of the hadith as well as its relevance in society.